Pembelajaran Gitar Berbasis Daring Di SMA Negeri 5 Tanjung Jabung Timur - Mourent Aulia Abadi; Harisnal Hadi (FBS Universitas Negeri Padang, 2021)
This study aims to describe the implementation of online learning on cultural arts learning, especially music arts that discuss about western music guitar material class XI IPA II at SMAN 5 Tanjung Jabung Timur. This research includes qualitative research using descriptive approaches. This research instrument is a researcher itself and assisted with supporting instruments such as stationery and mobile phones. Data collection techniques are conducted by interviewing, observation and documentation. Based on the results of the research, it can be concluded that the implementation of online-based guitar learning at SMAN 5 Tanjung Jabung Timur is using Whatsapp and Google Classroom media. This is recommended by the Principal of SMAN 5 Tanjung Jabung Timur to help and get around online learning so that teaching and learning activities continue to run smoothly even in remote circumstances. Online guitar learning planning is done online, not yet felt maximum because teachers do not make rpp specifically for use in the online learning process. During the guitar-based learning process, there were some obstacles. The results of online-based guitar learning in class XI IPA III are less effective and less maximal because during the learning process there is less attention to standards in the preparation of online learning materials.